The Role of Local Institutions in Adaptation to Climate Change - Agrawal, Arun (World Bank, Washington, DC, 2017)
This review focuses on the role of local institutions in adaptation to climate change. It does so under the belief that climate impacts will affect disadvantaged social groups more disproportionately, and that local institutions centrally influence how different social groups gain access to and are able to use assets and resources. It suggests that adaptation to climate change is inevitably local and that institutions influence adaptation and climate vulnerability in three critical ways: a) they structure impacts and vulnerability, b) they mediate between individual and collective responses to climate impacts and thereby shape outcomes of adaptation, and c) they act as the means of delivery of external resources to facilitate adaptation, and thus govern access to such resources. In focusing on local institutions, the review fills two glaring gaps in the existing understanding about institutions and climate change: the lack of middle-range theories of adaptation practices to help frame policy debates, and the absence of comparative empirical studies of adaptation to support policy interventions. To contribute to middle-range theoretical knowledge about climate change the review develops a conceptual framework to understand and classify the adaptation practices of the rural poor, view the institutional structuring of adaptation, and examine the types of external support interventions that local institutions inevitably channel. The review proposes a focus on different forms of mobility, storage, diversification, communal pooling, and market exchange in rural settings as the basic mechanisms through which households address riskiness of livelihoods. Using the familiar typology of public, private, and civil society institutions the review proposes an institutional linkages framework that highlights the role of institutional partnerships in facilitating adaptation and drawing from social network analysis it presents a conceptual toolkit to analyze institutional partnerships and their impacts on resource access of vulnerable social groups. In examining the role of institutions in channeling financial, information and technological, leadership, and policy interventions into rural areas, the review highlights that institutions are critical leverage points through which to determine the direction and magnitude of flows of resources to different social groups.